The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1093/bja/aew031
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound assessment of gastric volume in children after drinking carbohydrate-containing fluids

Abstract: cris.nih.go.kr (KCT0001546).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 37 publications
4
47
0
4
Order By: Relevance
“…Multiple studies, using various methodologies, have reported a linear correlation between antral cross‐sectional area and gastric volume, with correlation coefficients ranging from 0.6 to 0.91 . Using a similar approach of controlled fluid ingestion to our current study, but with only two volumes of 250 ml and 500 ml, Perlas et al showed a correlation coefficient of 0.86 .…”
Section: Discussionsupporting
confidence: 72%
“…Multiple studies, using various methodologies, have reported a linear correlation between antral cross‐sectional area and gastric volume, with correlation coefficients ranging from 0.6 to 0.91 . Using a similar approach of controlled fluid ingestion to our current study, but with only two volumes of 250 ml and 500 ml, Perlas et al showed a correlation coefficient of 0.86 .…”
Section: Discussionsupporting
confidence: 72%
“…Ultrasound assessment in children confirms that 10–15 ml.kg −1 clear fluids given 2 h pre‐operatively results in a reduction rather than an increase in antral volume by the time of induction .…”
Section: Childrenmentioning
confidence: 77%
“…Promising emerging areas of study in paediatrics are the use of a bed‐side ultrasound to ascertain residual gastric contents , perhaps as a potential tool in modifying the induction technique in the emergency setting . We have come a long way since the nil‐from‐midnight days, but there is still much more refinement to the pre‐operative fasting process to be done.…”
Section: Childrenmentioning
confidence: 99%
“…10 In addition, such carbohydrate loading may help to reduce thirst, hunger, and anxiety. 11 Initial promising reports using high-carbohydrate beverages in children are published, 12 but investigations where gastric content is directly measured are not available. Therefore, we designed a randomised controlled trial to assess how a commercially available carbohydrate beverage, labelled as a dietary supplement for preoperative oral administration, would affect the gastric contents and various parameters of perioperative discomfort in children subjected to general anaesthesia.…”
Section: Editor's Key Pointsmentioning
confidence: 99%